Pre-Procedure Intervention of Subclinical Hypothyroidism: Case Report - Tantri, Anita Ratnasari; Santi Syafril (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2022)
Background: Subclinical hypothyroidism (SH) is a very common disorder in the general population. In patients with known hypothyroidism or hypothyroidism who have been undergoing treatment, a TSH test should be included in the preoperative assessment to determine the adequacy of treatment and to ensure that thyroid therapy is optimized before surgery. Case Presentation: A 39 years old woman complains about a weakness that has been 4 years interfering with activities. Shortness of breath if doing strenuous activities, walking long distances, and climbing stairs, and shortness of breath decreases after rest. Sore throat found since 1 week of hospitalization, and fever for 1 day. A lump in the neck is not found. Previously, the patient had been treated for 8 days in the Department of Cardiology and planned the installation of a temporary pacemaker due to bradycardia that persisted until cardiac arrest. Conclusion: Subclinical hypothyroid patients undergoing pre-procedure intervention are predisposed to anemia, electrophysiologic disturbances, and hypotension, all of which can precipitate cardiovascular collapse. The goal of therapy in the perioperative patient with thyroid dysfunction centers around the attempt to normalize hormone levels before surgical intervention whenever possible and, when that is not feasible, to use other measures that will maximize hemodynamic stability and prevent decompensation. Â